Physiological and electromyographic responses during 40-km cycling time trial: Relationship to muscle coordination and performance - Bini, R. R.; Carpes, F. P.; Diefenthaeler, F.; Mota, C. B.; Guimaraes, A. C. S. (Journal of Science and Medicine in Sport, 2008)
The purpose of this study was to compare the oxygen uptake (VO2), respiratory exchange ratio (RER), cadence and muscle activity during cycling a 40-km time trial (TT), and to analyse the relationship between muscle activity and power output (PO). Eight triathletes cycled a 40-km TT on their own bicycles, which were mounted on a stationary cycle simulator. The VO2, RER and muscle activity (electromyography, EMG) from tibialis anterior (TA), gastrocnemius medialis (GA), biceps femoris (BF), rectus femoris (RF) and vastus lateralis (VL) of the lower limb were collected. The PO was recorded from the cycle simulator. The data were collected at the 3rd, 10th, 20th, 30th and 38th km. The root mean square envelope (RMS) of EMG was calculated. The VO2 and PO presented a significant increase at the 38th km (45.23 ± 8.35 ml kg min-1 and 107 ± 7.11% of mean PO of 40-km, respectively) compared to the 3rd km (38.12 ± 5.98 ml kg min-1 and 92 ± 8.30% of mean PO of 40-km, respectively). There were no significant changes in cadence and RER throughout the TT. The VL was the only muscle that presented significant increases in the RMS at the 10th km (22.56 ± 3.05% max), 20th km (23.64 ± 2.52% max), 30th km (25.27 ± 3.00% max), and 38th km (26.28 ± 3.57%max) when compared to the 3rd km (21.03 ± 1.88%max). The RMS of VL and RF presented a strong relationship to PO (r = 0.89 and 0.86, respectively, p < 0.05). The muscular steady state reported for cycling a 30-min TT seems to occur in the 40-km TT, for almost all assessed muscles, probably in attempt to avoid premature muscle fatigue.